A study to compare the clinical outcome of sublingual and vaginal misoprostol in the medical management of missed miscarriage in first trimester - Lamba, Akanksha; Kaur, Ramanjeet; Sardana, Priya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Objective of the study was to compare the efficacy, outcome and side effects of sublingual and vaginal misoprostol for the medical management of missed miscarriage. Methods: Fifty women diagnosed as having missed miscarriage of gestational age less than 20 weeks were randomized to vaginal or sublingual route of drug administration by lottery method (random sampling) A total number of 25 cases in each of the two groups were considered. Women in Group A received 400 microgram of misoprostol sublingually every four hours for a maximum of 5 doses and those in Group B received 400 microgram of misoprostol vaginally every four hours for a maximum of 5 doses. The primary outcome measures were, complete evacuation of products of conception, mean induction to delivery time and the occurrence of side effects. Results: In complete evacuation rates between the sublingual misoprostol and the vaginal misoprostol groups there was no statistically significant difference. Mean induction to delivery time was also similar for both groups as was the total number of doses required. As far as Side effects were concerned, Diarrhea was the major frequent side effect of sublingual misoprostol seen in 32% cases against only 12% cases with vaginal misoprostol. Conclusions: The effectiveness of Sublingual misoprostol is comparable to that of vaginal misoprostol for medical management of missed miscarriage but is associated with an increased risk of side effects especially diarrhoea.